Percutaneous Balloon Compression Technique using Intraoperative DynaCT for the Treatment of Trigeminal Neuralgia: Initial Experience. (16th November 2020) - Jain, Aakangsha; Ali, Assad; Obrzut, Michal; Adada, Badih; Borghei-Razavi, Hamid
Abstract: INTRODUCTION: Percutaneous balloon compression (BC) is a well-established technique that can provide immediate therapeutic relief to patients suffering from trigeminal neuralgia (TN). Intraoperative DynaCT allows for easier positioning and insertion of the needle through the FO by providing three-dimensional images for needle guidance. DynaCT also allows for intraoperative mapping of the course of the carotid artery andother vital structures, significantly increasing the safety of the procedure. METHODS: In this study, DynaCT was used to perform BC in 10 consecutive patients with TN. The course of the carotid artery was mapped and the needle path was pre-planned using DynaCT. The FO was accessed with a single needle pass with needle-guided bi-plane fluoroscopy. In selected cases, additional DynaCT was used to confirm of the final needle position within the foramen ovale prior to balloon inflation. RESULTS: All 10 consecutive patients reported improvement in pain and decreased sensation in V2 and V3 branches of the trigeminal nerve following the procedure. There were no complications, and each patient achieved a quick recovery. One patient reported persistent pain in the V1 distribution after a first BC procedure. This paitent underwent a second procedure with DynaCT, with the needle aimed more medially and anteriororly and reported V1 pain relief. CONCLUSION: In our initial experience, the DynaCT-guided percutaneous BC approach showed to be effective in significantly improving patient's pain. The advantages of this technique include a single needle pass, less procedure related trauma, avoidance of vessel injury, and quicker patient recovery. Precise placement of the balloon into different aspects of the foramen ovale can improve patient outcomes by more selective targeting of trigeminal nerve branches.